“Ico-Alone” single nocturnal exchange to initiate peritoneal dialysis in patients with residual renal function–Five year, single centre experience - Jeloka, T. (Medknow Publications & Media Pvt Ltd, 2013)
We analyzed the outcome of incremental dialysis with single nocturnal icodextrin exchange peritoneal dialysis (PD) as the initial treatment for end-stage kidney failure in patients who have significant residual renal function. All adult patients opting for PD as renal replacement therapy, having residual renal function, and urinary KT/V of 1.0 were offered incremental dialysis with single nocturnal icodextrin exchange as initial treatment. Adequacy of dialysis was calculated at 1, 3, and 6 months and then 6 monthly. Patients were shifted to conventional PD if short of adequacy or if clinically indicated. Median period on “Ico-alone,” peritonitis, exit site infection rates, and patient survival, while on this protocol, were calculated. These outcomes were compared with the cohort of contemporary patients on conventional PD. Thirteen patients were initiated on “Ico-alone” dialysis between October 2006 and October 2011. The baseline characteristics were similar when compared with cohort of conventional PD patients, except urine volume, which was more in “Ico-alone” group (1265 ± 316 vs. 551 ± 504, P = 0.000). Total KT/V at 3 months (1.63 ± 0.6 vs. 1.7 ± 0.2, P = 0.6) and at 1 year (1.64 ± 0.5 vs. 1.53 ± 0.3, P = 0.6) was similar to the cohort of conventional PD patients. Median period on “Ico-alone” was 9.6 months. Peritonitis rate was 1 episode in 56.22 vs 25.29 patient-months and exit site infection was 1 episode in 56.2 vs 189.71 patient-months in “Ico-alone” and conventional group, respectively. Patient survival was 42.84 months in “Ico-alone” vs 25.29 months in conventional dialysis (P = 0.01). In conclusion, single icodextrin exchange offers adequate dialysis in patients with residual renal function (KT/V = 1) for a median period of 9 months.